Rancang Bangun Kereta Gantung Pengangkut Produk Hasil Pertanian - Setiawan, Muhammad Gandi; Tamrin, Tamrin; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2022)
Problems in the agricultural sector are not only in the process of plant maintenance activities, but also because of the location of agricultural land that is not always easily accessible such as in mountainous areas and mountain slopes. This is certainly one of the obstacles for farmers in terms of transporting agricultural products. Cable cars are one of the innovations of transportation equipment that transport agricultural products that can be developed to help and facilitate the work of farmers effectively and efficiently. This study aims to design and make cable cars as a means of transporting agricultural products and performing performance tests on tools. This research was conducted in September-October 2018 at the Laboratory of Agricultural Equipment and Machinery, Agricultural Engineering Department, Faculty of Agriculture, University of Lampung. This research begins with the stage of determining the basic design of tools, designing tools, making tools, testing tools, observing and retrieving data. The mechanism of action of this tool is to hang the rail frame using a rope that is tied to a metal iron to a support pole at a certain slope angle. Then on the frame of the train there is an iron hook as a means of hanging a net that has been filled with loads. The way to operate the tool is by manually pulling it. The results showed that the no-load tool performance test took 6.08 seconds, with a load of 10 kg which was 6.86 seconds, a load of 20 kg at 8.10 seconds, and a load of 30 kg at 10.28 seconds. The slope angle obtained at 48 cm slope height is 8.53 °, the slope height of 57 cm is 6.84 °, and the slope height of 66 cm is 5.71 °. The cable car transporting agricultural products is 1200 cm long, 10 cm wide, and 16 cm high. The maximum load capacity that can be operated by the tool is 30 kg. Keywords: Agricultural Produce, Cable Car, Manual.